Ninth Edition of the Tumor, Node, and Metastasis Classification of Lung Cancer - Fong, Kwun M.; Olive, Gerry; Marshall, Henry M.; Rami-Porta, Ramon; Detterbeck, Frank (Seminars in Respiratory and Critical Care Medicine, 2025)
This paper reviews the development of the current edition (Ninth) of the Tumor, Node, and Metastasis (TNM) classification of lung cancer. This classification was proposed from the analyses of a global database of 124,581 patients diagnosed between 2011 and 2019 established by The International Association of the Study of Lung Cancer. Overall survival was calculated using the Kaplan–Meier method, and prognosis assessed using multivariable-adjusted Cox proportional hazards regression to guide proposed changes to the Eighth Edition TNM classification. The innovations in the Ninth Edition TNM are: the T categories remain the same as in the Eighth Edition but descriptors previously considered separately were transferred to the official list of descriptors; the N2 category was subdivided into N2a (involvement of a single N2 station) and N2b (involvement of multiple N2 stations); the M1c category was subdivided into M1c1 (multiple extrathoracic metastases in a single organ system) and M1c2 (multiple extrathoracic metastases in multiple organ systems); and tumor cells spread through air spaces was introduced as an additional pathological descriptor. The Ninth Edition TNM classification of lung cancer aids in the understanding of the prognostic relevance of the anatomical extent of lung cancer but requires thorough clinical and pathological evaluations to benefit from the changes in clinical practice and in research.
Keywords: lung cancer; lung cancer stages; nonsmall cell lung cancer; TNM classification